PENGEMBANGAN MODUL MATEMATIKA BERBASIS RME UNTUK SISWA KELAS 1 SEKOLAH DASAR - Ira Mira; Rachmiati, Wida; Wahyu Wibowo, Eko (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
Based on observations, there are low mathematics scores for measurement material in 2 different schools. This happened due to the COVID 19 factor and lack of parental guidance. Therefore, as a reference, researchers developed RME-based mathematics teaching materials in the form of realistic mathematics education-based modules. This research uses the R&D method. aims to determine the procedures, feasibility and effectiveness of the module. Based on the research carried out, the results of the research are: procedures carried out based on the ADDIE model, validation from media and material experts respectively 75% and 76%. And this product is considered effective because it can liven up the classroom atmosphere and get student and teacher questionnaire scores of 100% and 85% respectively.